1998
DOI: 10.3208/sandf.38.special_69
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Evaluating Residual Post-Liquefaction Ground Settlement and Horizontal Displacement

Abstract: During the 1995 Hyogoken-Nambu earthquake, large vertical residual ground settlements and horizontal displacements extensively occurred in liquefied soils behind caisson-type quay walls where lateral movements of the walls towards sea were led by strong seismic shaking. Case studies further show that both significant vertical residual ground settlements and horizontal displacements were also induced by this earthquake in liquefied level sandy ground with a sufficiently large lateral extent where no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…It should be noted that higher values of maximum likelihood and lower values of standard deviation are also indicators of a better model. As the values of the calibration coefficient, θ, presented in Table 19.1 implies, existing methods of Shamoto et al (1998), Tokimatsu and Seed (1984), and the proposed methodology under-predict the actual settlements by a factor of 1.91, 1.45 and 1.15, respectively. Similarly, Wu and Seed (2004), and Ishihara and Yoshimine (1992) over-predict settlements and need to be corrected by a factor of 0.98 and 0.90.…”
Section: Assessment Of Post-cyclic Settlementsmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that higher values of maximum likelihood and lower values of standard deviation are also indicators of a better model. As the values of the calibration coefficient, θ, presented in Table 19.1 implies, existing methods of Shamoto et al (1998), Tokimatsu and Seed (1984), and the proposed methodology under-predict the actual settlements by a factor of 1.91, 1.45 and 1.15, respectively. Similarly, Wu and Seed (2004), and Ishihara and Yoshimine (1992) over-predict settlements and need to be corrected by a factor of 0.98 and 0.90.…”
Section: Assessment Of Post-cyclic Settlementsmentioning
confidence: 99%
“…The proposed method was calibrated via 49 well-documented cyclically-induced ground settlement case histories from seven different earthquakes. Within the confines of that study, performance of the widely used methods of Tokimatsu and Seed (1984), Ishihara and Yoshimine (1992), Shamoto et al (1998), Wu and Seed (2004) were comparatively evaluated. It was concluded that the proposed methodology, details of which will be given next, produced more accurate and precise settlement estimations compared to all other efforts.…”
Section: Assessment Of Post-cyclic Settlementsmentioning
confidence: 99%
See 3 more Smart Citations